Aero-structural optimization-based tailoring of bridge deck geometry. (1st November 2022) - Cid Montoya, M.; Hernández, S.; Kareem, A.
Abstract: The deck cross-section is usually identified in engineering practice as the most important design variable in the wind-resistant design of long-span bridges. This is certainly true in most cases since it controls the aerodynamic and mechanical contribution of the deck to the global bridge performance. However, the effectiveness of deck shape modifications to handle the aeroelastic constraints is highly influenced by the aeroelastic performance requirements. This paper seeks to delve into the aero-structural design optimization of long-span bridges by analyzing possible design scenarios depending on the ability of the deck shape to meet the imposed aeroelastic requirements. A long-span cable-stayed bridge is optimized focusing on the buffeting response and considering different sets of limit values for the design constraints. According to the effectiveness of the deck shape design variables and other size design variables to manage the aeroelastic design constraints, three types of aero-structural optimization problems are identified: type I, aeroelastic constraints are not active and structural constraints drive the design; type II, aeroelastic constraints are active and effectively controlled by deck shape modifications; and type III, aeroelastic constraints are active and demand both shape and size modifications. The engineering significance for practical design is discussed. Highlights: The aero-structural shape and size optimization problem is addressed considering several sets of buffeting constraints. Optimization results provide useful guidelines for the buffeting-resistant design of single-box deck bridges. The influence of the aeroelastic performance requirements on the effectiveness of deck shape modifications is studied. Three different types of aero-structural optimization problems have been identified.